Exploring curiosity and critical thinking skills for prospective biology teacher - Nurdiana Nurdiana; Hunaepi Hunaepi; Muhammad Ikhsan; Hadi Suwono; Sulisetijono Sulisetijono (Institute of Advanced Engineering and Science, 2023)
Curiosity and critical thinking as one of the characteristics and skills developed in the goals of Indonesian education and 21st-century learning. Curiosity is a driving force for intrinsic motivation to explore behavior and gain new understanding and knowledge through observation. Curiosity and critical thinking skills are the needs of every individual to explore sciences such as biology. This study’s aim is to explore the curiosity and critical thinking skills of prospective biology teacher students. This research is a qualitative descriptive study with a survey method. The sample of this study amounted to 150 students who were taken using purposive random sampling. Curiosity data was collected using science curiosity in learning environments (SCILE) and critical thinking skills were collected using the developed instrument. The data obtained were analyzed using the partial least square program to determine the contribution of gender to scientific curiosity (SC) and critical thinking skills. The results of the analysis show that gender contributes directly to critical thinking skills through SC on the stretching indicator. In general, SC needs to do research to find out the contribution of each critical thinking.